Nonparametric regression estimators in dual frame surveys. Issue 3 (4th March 2021) - Lu, Yan; Fu, Ye; Zhang, Guoyi
Abstract: Dual frame surveys, in which independent samples are selected from two frames to decrease survey costs or to improve coverage, can present challenges for regression estimation because of complex designs and unknown degree of overlap. In this research, we developed three nonparametric regression estimators in dual frame surveys and investigated their asymptotic properties. Simulation results show that all the proposed methods work well.